Analisis Strategi Bisnis pada Toko Budiman Sembako Kecamatan Sungai Tebelian, Kalimantan Barat: analisis strategi Bisnis - anis fitri wati (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2022)
Abstract NZE Fresh Fruits fruit shop is a shop that sells various kinds of fresh fruits. Due to the intense competition in the fruit trade, this fruit shop has its own business strategy. Business strategy aims to achieve long-term goals to be achieved and find the company's position in the industry so that the company can protect itself against competitive pressures. This study aims to analyze business strategies in surviving the increasingly fierce competitive pressures in the market at the NZE Fresh Fruits fruit shop on Jalan Dr. Wahidin near the morning market in Pontianak City. This research was conducted using descriptive qualitative methods by prioritizing interview methods and observation instruments, namely direct observations and assisted by literature studies. This research was conducted by analyzing the external environment and the internal environment through business functions. Then do a SWOT analysis, so that it can produce several alternatives in developing a business strategy for the NZE Fresh Fruits fruit shop. The results of this study indicate that the right strategy for NZE Fresh Fruits fruit shops is the intensive strategy. With these alternative strategies the company can achieve the desired goals and can survive in the face of competitive pressures in the market.